Packet Scheduling Algorithm Considering a Minimum Bit Rate for Non‐realtime Traffic in an OFDMA/FDD‐Based Mobile Internet Access System - Kim, Dong‐Hoi; Ryu, Byung‐Han; Kang, Chung‐Gu (ETRI journal, 2004)
In this letter, we consider a new packet scheduling algorithm for an orthogonal frequency division multiplexing access/frequency division duplex (OFDMA/FDD)‐based system, e.g., mobile broadband wireless access or high‐speed portable internet systems, in which the radio resources of both time and frequency slots are dynamically shared by all users under a proper scheduling policy. Our design objective is to increase the number of non‐realtime service (e.g., WWW) users that can be supported in the system, especially when the minimum bit rate requirement is imposed on them. The simulation results show that our proposed algorithm can provide a significant improvement in the average outage probability performance for the NRT service, i.e., significantly increasing the number of NRT users without much compromising of the cell throughput.